Swelling in pregnant women: a disease or a norm? - V E Radzinsky; T V Hapova; A S Olenev; A V Solovieva (IP Berlin A.V., 2014)
During pregnancy the effects of a number of predisposing factors (influence of progesterone, a violation of the passage of urine, the occurrence of vesicoureteral reflux) often lead to exacerbation of chronic diseases of the urinary tract, the development of eye and preeclampsia. This has an adverse impact on the course of pregnancy and perinatal outcomes. The Multicenter study «Evaluation of efficacy, safety and tolerability of cranberry extract in soft capsules Iuravit (biologically active additive to food) for prophylaxis and complex therapy of urinary tract infections in women during pregnancy» in cases of 195 women showed high efficacy, tolerability, a small number of side effects (5,6% of women), and worsening of urinary tract infections in 4,6% (mostly due to a violation of the outflow of urine and indications for stenting ureters). It allows to recommend the use of cranberry extract Juravit as prophylaxis in pregnant women with diseases of the urinary tract.